ANALISIS PENGENDALIAN KUALITAS WINE MENGGUNAKAN X̄–R CONTROL CHART - Carles Syahputra Hulu; Nia Rizkita Tambunan; Togi Supriadi Supriadi Sianturi; Zulkhairi Zulkhairi Zulkhairi (Universitas Lambung Mangkurat, 2026)
Quality control is a critical aspect of the production process to ensure that the resulting products meet established standards. In the wine industry, quality is significantly influenced by chemical parameters such as pH, density, and alcohol content. This study aims to analyze the stability and consistency of these parameters using the X̄–R Control Chart method. The research utilizes secondary data from the Kaggle dataset, which contains physicochemical characteristics of wine. The methodology involves grouping data into subgroups, calculating control limits using statistical constants, and plotting the results to evaluate process conditions. The results indicate that the X̄–R Control Chart is effective in monitoring process changes over time, allowing for early detection of variations that could affect product quality. Parameters such as pH, density, and alcohol content show specific patterns that reflect the stability of the fermentation and production processes. By implementing this method, producers can maintain product consistency and take corrective actions before the product fails to meet specifications. Thus, the application of Statistical Quality Control (SQC) provides an objective and efficient approach to ensuring high-quality wine production.